The Effect of Work Environment and Salary on Motivation and The Impact on Employee Job Satisfaction in Indonesia Tourism Development Corporation (Persero) - Ahmad Setiawan Nuraya; Dewanti Pratiwi (Indonesia Banking School, 2017)
The purpose of this research is to study about work environment, salary, motivation, and job satisfaction. This study is to analyzes the influence of work environment and salary on motivation and the effect of job satisfaction. The object of this research is Indonesia Tourism Development Corporation (Persero). The population in this study we’re all permanent employee that has been working more than one year that consist of 117 people, the total of the respondents are 91 in Indonesia Tourism Development Corporation (Persero). This research use questionnaire to collect data from respondents. All data analyzed using Partial Least Square (PLS) with Smart PLS 3.0 software. The result of this research shows that working environment and salary have significant influences on motivation and motivation have significant influence on Job satisfaction.